2011
DOI: 10.1186/cc10284
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic goal-directed therapy and postoperative infections: earlier is better. a systematic review and meta-analysis

Abstract: IntroductionInfectious complications are the main causes of postoperative morbidity. The early timing of their promoting factors is the rationale for perioperative strategies attempting to reduce them. Our aim was to determine the effects of perioperative haemodynamic goal-directed therapy on postoperative infection rates.MethodsWe performed a systematic review and meta-analysis. MEDLINE, EMBASE, The Cochrane Library and the DARE databases were searched up to March 2011. Randomised, controlled trials of major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
74
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(80 citation statements)
references
References 75 publications
3
74
1
2
Order By: Relevance
“…There is consistent evidence that an optimisation strategy can improve outcomes as long as it is delivered before the onset of cell ischaemia and organ failure [125,126]. Recent evidence for immunomodulating effects are conflicting [127,128], and some workers have demonstrated other benefits e.g. on gastro-intestinal function [129].…”
Section: Managing the Circulation And Shockmentioning
confidence: 99%
“…There is consistent evidence that an optimisation strategy can improve outcomes as long as it is delivered before the onset of cell ischaemia and organ failure [125,126]. Recent evidence for immunomodulating effects are conflicting [127,128], and some workers have demonstrated other benefits e.g. on gastro-intestinal function [129].…”
Section: Managing the Circulation And Shockmentioning
confidence: 99%
“…Interest was generated by Shoemaker et al [72], who demonstrated morbidity and mortality benefits, when a goal-directed approach was applied to the perioperative care of high-risk surgical patients. Some subsequent studies have shown reduced risk of infective complications [73], AKI [74], cardiovascular complications [75], pneumonia, and hospital length of stay [74]. However, others have found no benefit, in abdominal aortic surgery [76] or colorectal surgery [77].…”
Section: Goal-directed Approachesmentioning
confidence: 99%
“…In this issue of Anaesthesia, Stevens et al [1] provide more evidence for the complexity of tramadol usage. Tramadol was only licensed in the UK 30 years ago, yet in its short lifetime it has attracted a disproportionate amount of attention.…”
Section: Editorialmentioning
confidence: 99%
“…It has been suggested that early goal-directed haemodynamic optimisation, for instance by continuously measuring and optimising stroke volume, may lead to a decreased infection rate, fewer unwanted cardiac events and faster recovery of bowel function, with a reduction in postoperative morbidity [1][2][3][4]. However, the recommendation of the routine use of oesophageal Doppler in major surgery continues to generate ongoing discussion [5][6][7][8].…”
mentioning
confidence: 99%